Design Caisson Breakwaters in the Syrian Coast Based on Goda Equations - الجاسم معتز; امال حيدر (Latakia University Journal -Engineering Sciences Series, 2024)
Ports are exposed to forces that differ from other facilities, to maintain its performance and effectiveness, the engineering designs of facilities must be carefully studied, Protection facilities are considered one of the most important elements of the port because they provide a safe water area in which loading and unloading operations are perfect, designs for this type of breakwaters have been developed at five different depths according to the expected wave heights in the Syrian coast. The research dealt with the design of breakwaters facilities such as caisson breakwater type, due to its many advantages in protection ports. the design dimensions, pressures, forces, and moments resulting from the impact of waves on the breakwater were calculated, which helped to study the stability factors on sliding and overturning, as well as the bearing capacity of the rubble foundation at the base of the caisson block, and the study showed that the facilities according to the proposed designs are safe and capable of providing protection in the Syrian coast.